2009
DOI: 10.1097/jto.0b013e3181add877
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Neoadjuvant Therapy with Carboplatin, Gemcitabine plus Thalidomide for Stages IIB and III Non-small Cell Lung Cancer

Abstract: This neoadjuvant regimen was well tolerated and effective in inoperable NSCLC and warrants additional investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Two parallel non-randomised phase II studies in patients with malignant mesothelioma treated with single agent thalidomide or thalidomide combined with carboplatin and gemcitabine reported pre-treatment VEGF serum levels were prognostic, and increases in VEGF levels on treatment were associated with a worse prognosis (Kao et al , 2012). A small phase II trial of neo-adjuvant carboplatin–gemcitabine chemotherapy with thalidomide in 15 patients with stage IIB–IIIA NSCLC showed that a higher baseline IL-8 was associated with a significantly greater risk of disease recurrence post-operatively, although an increase in IL-8 after treatment was associated with a reduced risk of recurrence (Dudek et al , 2009). Biomarker levels in this study of patients with relatively low volume disease were lower than in our NSCLC patients with stage IIIB and IV disease.…”
Section: Discussionmentioning
confidence: 99%
“…Two parallel non-randomised phase II studies in patients with malignant mesothelioma treated with single agent thalidomide or thalidomide combined with carboplatin and gemcitabine reported pre-treatment VEGF serum levels were prognostic, and increases in VEGF levels on treatment were associated with a worse prognosis (Kao et al , 2012). A small phase II trial of neo-adjuvant carboplatin–gemcitabine chemotherapy with thalidomide in 15 patients with stage IIB–IIIA NSCLC showed that a higher baseline IL-8 was associated with a significantly greater risk of disease recurrence post-operatively, although an increase in IL-8 after treatment was associated with a reduced risk of recurrence (Dudek et al , 2009). Biomarker levels in this study of patients with relatively low volume disease were lower than in our NSCLC patients with stage IIIB and IV disease.…”
Section: Discussionmentioning
confidence: 99%
“…Neoadjuvant therapy aims to reduce tumor size and burden, while acting on occult micro-metastatic disease, thereby increasing the likelihood of downstaging and complete surgical resection, as well as reducing the risk of recurrence ( 5 ). Previous studies have demonstrated that neoadjuvant therapy could be a cornerstone towards improved efficacy and survival for patients ( 6 8 ).…”
Section: Introductionmentioning
confidence: 99%